Training guide administering Windows Server 2012 - Thomas, Orin 1973- (Microsoft Press, 2013)
Designed to help enterprise administrators develop real-world, job-role-specific skills--this Training Guide focuses on deploying and managing Windows Server 2012. Build hands-on expertise through a series of lessons, exercises, and suggested practices--and help maximize your performance on the job. This Microsoft Training Guide: Provides in-depth, hands-on training you take at your own pace Focuses on job-role-specific expertise for deploying and managing Windows Server 2012 Creates a foundation of skills which, along with on-the-job experience, can be measured by Microsoft Certification exams such as 70-411 Sharpen your skills. Increase your expertise. Deploy and update Windows Server 2012 Manage account policies and service accounts Configure name resolution Administer Active Directory Manage Group Policy application and infrastructure Work with Group Policy settings and preferences Administer network policies Configure the network to enable remote access Manage file services Monitor and audit Windows Server 2012.
Online resource; title from title page (Safari, viewed June 26, 2013)
Keywords: Microsoft Windows server -- Study guides -- Examinations; Operating systems (Computers) -- Study guides -- Examinations; Electronic data processing personnel -- Study guides -- Certification; Microsoft Windows server / Examinations / Study guides; Microsoft Windows server; Systèmes d'exploitation (Ordinateurs); Examens; Guides de l'étudiant; COMPUTERS; Operating Systems; General; Electronic data processing personnel; Certification; Examinations; Operating systems (Computers); Examinations; Study guides